2014
DOI: 10.1007/s12098-013-1310-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25 Hydroxy Vitamin D Insufficiency Associated with Bronchial Asthma in Lucknow, India

Abstract: 25 hydroxy vitamin D insufficiency is associated with bronchial asthma as well as its level of control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…This in agreement with [14], [23], [24] and15 study which showed statistically significant correlation between asthma control and vitamin D status [p value < 0.001].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This in agreement with [14], [23], [24] and15 study which showed statistically significant correlation between asthma control and vitamin D status [p value < 0.001].…”
Section: Discussionsupporting
confidence: 93%
“…The study showed the correlation between vitamin [D] level and asthma control in asthmatic children. our study was crosssectional study conducted on 60 asthmatic child aged 4-15 years old 80%of them were vitamin D deficient [ levels <20 ng/ml] and 20% were in insufficient range with levels [20][21][22][23][24][25][26][27][28][29][30] Our study reveiled statistically significant difference between serum vitamin D level and associated atopic conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Ten studies was selected to explore the association between vitamin D and FEV1% (r = 0.27, 95% CI = 0.22 to 0.33, p < 0.001; I2 = 93%, P < 0.001). Three studies [32, 42, 48] were regarded as homogeneous after a sensitivity analysis and were eliminated from the pooled result (r = 0.19, 95% CI = 0.13 to 0.26, p < 0.001; I2 = 42%, P = 0.11) (Fig. 3b).…”
Section: Resultsmentioning
confidence: 99%
“…[17] Likewise, an Indian study done in asthmatic children aged 1–15 years has shown between serum 25-hydroxy Vitamin D (25(OH)D) insufficiency and level of asthma control. [18]…”
Section: Introductionmentioning
confidence: 99%